Mental Readiness of Physical Education Students for Odd Semester Lectures in 2023 - Yahya Eko Nopiyanto; Septian Raibowo; Andika Prabowo; Ipa Sari Kardi; Ibrahim (Indonesian Journal of Physical Education and Sport Science)
Studi purpose. Mental preparation affects a person's performance in achieving and realizing their hopes, especially in the fields of education and sports. This study aims to reveal the level of mental readiness of physical education students in attending lectures in the odd semester of 2023. This research seeks to reveal the level of mental readiness of physical education students to attend lectures in the odd semester of 2023.